Una nueva técnica viverística para la introducción de plantones de DE QUERCUS SPP. EN CLIMA SECO Y SEMIÁRIDO - Vilagrosa, A; SEVA, J P; Valdecantos, a; HERNÁNDEZ, N; CORTINA, J; Bellot, J; Vallejo, V R (II Congreso Forestal Español, 1997)
We present a new technique to improve the establishment of Quercus spp. seedlings in dry and semiarid environments. It is based on the use of pre-germinated acorns transplanted in biodegradable nursery container which are transferred to the field befo re root pruning and upward root growth occurs. In this experiment we also tested the use of tree-shelters.
Keywords: bellotas pregerminadas (voyant); clima mediterráneo; plantones; Quercus spp.; supervivencia